Impact of water vapor on stratospheric temperature after the 2022 Hunga Tonga eruption: direct radiative cooling versus indirect warming by facilitating large particle formation - Xi Chen; Jun Wang; Meng Zhou; Zhendong Lu; Lyatt Jaegle; Luke D. Oman; Ghassan Taha (npj Climate and Atmospheric Science)
Abstract The unprecedented water vapor amount (WV, 150–160 Tg) injected by the 2022 eruption of Hunga Tonga–Hunga Haʻapai not only directly cooled the stratosphere, but also facilitated the formation and growth of sulfate particles, indirectly heating it. Here, we developed analytical models constrained by satellite observations to quantify these contrasting roles of WV in stratospheric temperature perturbations. Our analysis revealed that condensation and nucleation processes facilitated by abundant WV accounted for ~90% of the observed particle radius growth, from 0.1–0.2 µm to 0.35–0.45 µm. Despite increased aerosol extinction due to particle growth, a cooling of up to −4 K was observed in the mid-stratosphere, persisting for over a year since February, with over 60% attributed to WV radiative cooling. Conversely, in the lower stratosphere, ~50% of the observed 1–2 K warming was attributed to the radiative heating of large particles that formed in upper layers and settled down gravitationally.